Alsterpaullone, a Cyclin-Dependent Kinase Inhibitor, Mediated Toxicity in HeLa Cells through Apoptosis-Inducing Effect - Chunying Cui; Yuji Wang; Yaonan Wang; Ming Zhao; Shiqi Peng (Journal of Analytical Methods in Chemistry)
Alsterpaullone, a small molecule cyclin-dependent kinase (CDK) inhibitor, regulates the cell cycle progression. Beyond death-inducing properties, we identified the effect of alsterpaullone on cycle procedure and apoptosis of HeLa cell. It was found that alsterpaullone inhibited HeLa cells in a time-dependent (0–72 h) and dose-dependent (0–30 μM) manner. In the presence of alsterpaullone, HeLa cells were arrested in G2/M prior to undergoing apoptosis via a mechanism that is involved in the regulation of various antiapoptotic genes, DNA-repair, transcription, and cell cycle progression. Compared to controls, alsterpaullone effectively prevented HeLa cells from entering S-phase. These potential therapeutic efficacies could be correlated with the activation of caspase-3.